2009
DOI: 10.1007/s00213-009-1526-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel touchscreen-automated paired-associate learning (PAL) task sensitive to pharmacological manipulation of the hippocampus: a translational rodent model of cognitive impairments in neurodegenerative disease

Abstract: De-activation of the hippocampus caused impairments in a PAL task. The selective nature of this effect (only one of the two tasks was impaired), suggests the effect is specific to cognition and cannot be attributed to gross impairments (changes in visual learning). The pattern of results suggests that rodent PAL may be suitable as a translational model of PAL in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
187
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(202 citation statements)
references
References 61 publications
5
187
1
1
Order By: Relevance
“…dPAL has already been shown to be hippocampus dependent in rats and mice (Talpos et al 2009;Kim et al 2015). We found that the new protocol with overlearning did not affect the hippocampal dependency of this task.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…dPAL has already been shown to be hippocampus dependent in rats and mice (Talpos et al 2009;Kim et al 2015). We found that the new protocol with overlearning did not affect the hippocampal dependency of this task.…”
Section: Discussionmentioning
confidence: 59%
“…The basic rules for these two tasks were the same as previously described (Talpos et al 2009). When mice touched a correct stimulus, they received the liquid reward, and an ITI (15 s) was introduced.…”
Section: Spal and Dpalmentioning
confidence: 99%
See 3 more Smart Citations